Characterisation of catchment runoff pollutants from sub-urban areas in South Johor - 347723 Wan Mokhtar Wan Nawang; Mohd. Azraai Kassim, 1958-; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Awam; International Conference on Environment and Development (1994 : Kuala Lumpur)
10